2004
DOI: 10.1373/clinchem.2004.038232
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immunoassays for Detection of Intact and Cleaved Forms of the Urokinase Receptor

Abstract: Results: The limits of quantification (CV <20%) determined by adding the proteins to uPAR-depleted plasma were <3 pmol/L in all three assays. The interassay CVs in plasma with added analytes were <11%, and recoveries were between 93% and 105%. Cross-reactivities of purified proteins in the three TR-FIAs were no more than 4%. Studies on chymotrypsin cleavage of uPAR and size-exclusion chromatography of plasma with and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 35 publications
1
68
0
1
Order By: Relevance
“…Thus, biological variables should probably not be considered in isolation; more information can be derived from markers in combination. Markers that may be useful for analysis of PCa include the prostate-specific tissue kallikreins or other markers of local cancer progression, such as TGF-␤ 1 , interleukin-6 receptor (30 ), and the urokinase-like plasminogen activation cascade (31,32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biological variables should probably not be considered in isolation; more information can be derived from markers in combination. Markers that may be useful for analysis of PCa include the prostate-specific tissue kallikreins or other markers of local cancer progression, such as TGF-␤ 1 , interleukin-6 receptor (30 ), and the urokinase-like plasminogen activation cascade (31,32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assay design, performance characteristics and measurements of serum-levels using three uPAR immunoassays, TR-FIA 1, 2 and 3, designed for the highly sensitive and specific measurement of suPAR(I-III), suPAR(I-III) 1 suPAR(II-III) and suPAR(I) have been previously described in very extensive detail. 15,16 …”
Section: Volumetric Analysis Of the Prostate Glandmentioning
confidence: 99%
“…Thus, the concentrations of the individual cleaved uPAR forms could be indicators of the activity of the plasminogen activation system, and the cleavage products may be stronger prognostic markers than the total amount of the uPAR forms. To test this hypothesis, we designed specific immunoassays to measure the individual uPAR forms (14 ). These assays demonstrated that the uPAR(I) concentration is a stronger prognostic factor than the total concentration of the uPAR forms (15 ).…”
mentioning
confidence: 99%
“…Our aim in the present study was to identify monoclonal antibodies (mAbs) with increased affinities for uPAR(I) to enable the design of a TR-FIA with an improved functional sensitivity. The uPAR mAb R3 has previously been characterized (8,14 ). mAb R20 is derived from a fusion between myeloma cells and spleen cells from female NIHS mice deficient in uPAR and immunized with human recombinant soluble uPAR from transfected Chinese hamster ovary cells.…”
mentioning
confidence: 99%